Animal-based measures on fattening heavy pigs at the slaughterhouse and the association with animal welfare at the farm level: a preliminary study. (14th June 2019) - Maisano, A. M.; Luini, M.; Vitale, N.; Rota Nodari, S.; Scali, F.; Alborali, G. L.; Vezzoli, F.
Abstract : Monitoring animal welfare (AW ) in pig farms requires both proper indicators and a feasible approach. Animal-based measures (ABMs ) are well-established AW indicators. Furthermore, AW screening at the slaughterhouses could be useful for identifying problems on farm. The aim of this study was to evaluate ABMs at the slaughterhouse and, when possible, to compare these ABMs with those collected on the farm. The study was carried out in northern Italy in a commercial abattoir and in a sample of farms. Animal-based measures were recorded on pigs from 62 batches of 54 farms, during ante-mortem ( n =10 085 pigs) and post-mortem ( n =7952 pigs) inspections. Sixteen of 54 farms were selected to compare ABMs collected at the slaughterhouse with ABMs collected on the farm. Overall, 2295 pigs (mean pigs examined per farm 119±45) were inspected at the slaughterhouse (group S) and 420 pigs (mean pigs per farm 26±5) on the farm (group F). Non-animal-based measures were also collected at the 16 farms. Differences between groups S and F, at the animal level, were assessed by a two-tailed paired Wilcoxon–Mann–Whitney test. Differences at the site of observation level (farm and slaughterhouse) were assessed by Fisher's exact test using a hierarchical log-linear modelling for contingency tables. The most frequent ABMs at the slaughterhouse were manure on the body (47.7%), followed by dermatitis (28.0%), white spot (25.4%) and bursitis (24.7%). Recording ABMs at the slaughterhouse and on the farm usually yielded similar results; however, there were some exceptions. In particular, significant differences were found for non-uniformity of size ( P <0.05) and dermatitis ( P <0.001), which were higher at the slaughterhouse than on the farm. Results of log-linear modelling underlined the effect of the farm of origin on the percentage of pigs with bursitis, manure on the body and ear injuries that were observed at the slaughterhouse. In group S, significant associations between manure on the body and insufficient presence of clean and dry areas in the corresponding farm were found ( P <0.05). Although these results should be interpreted with care due to the limited sample of farms, the slaughterhouse could be a feasible site of observation of ABMs, which could then be integrated in monitoring of AW on farm. Considering the number of slaughtered batches per farm, it would be possible to repeat assessments several times throughout the year for each farm, which could help provide an index for the continuous monitoring of AW.